Depression, anxiety, stress, and fear of COVID-19 among Bangladeshi medical students during the first wave of the pandemic: a mixed-methods study - Ashiq, Md Ashiqur Rahman; Gupta, Pradip Sen; Jubayer Biswas, Md Abdullah Al; Ahmed, Nowreen; Sultana, Mst. Sadia; Ghosh, Bikona; Hasan, M. Tasdik (Frontiers in Psychiatry, 2023)
Aim This study aims to investigate depression, anxiety, stress, and fear of the COVID-19 pandemic and the associated risk factors among Bangladeshi medical students. It also explored qualitative insights on mental health from medical students during the first wave of the pandemic. Methods This mixed-methods study was conducted online in Bangladesh from June 2020 to September 2020. Participants were Bangladeshi medical students from the first year to the final year. The quantitative part included a structured online survey. One focus group discussion (FGD) was organized using the Zoom platform to collect qualitative insights from the students. To determine levels of stress, anxiety, and depression, the Bangla-validated version of the Depression, Anxiety, and Stress Scale 21 (DASS-21) was used. A 7-item and Bangla-validated Fear of COVID-19 Scale, also known as FCV-19S, was used to explore the COVID-19-specific fear of the students. A semi-structured topic guide was used for exploring the qualitative insights of medical students' perceptions of fear of COVID-19, mental health impacts during COVID-19, overall recommendations to support students, and the impact of the pandemic on the future of the medical curriculum. Results The study reported that 51.20%, 59.40%, and 64% of the 406 respondents had moderate to severe stress, anxiety, and depressive symptoms, respectively, according to the DASS-21. The mean fear score for the COVID-19 scale was 19.4 (SD 6.4). Respondents with family members aged 50 years or older (B = 2.1; CI: 0.3-3.9) and those who had infected family members (B = 1.9; 95% CI: 0.1-3.7) exhibited a higher level of fear of COVID-19. Moreover, depression was associated with a history of having cancer among family members (AOR = 2.9, CI: 1.1-7.5), anxiety was strongly associated with having symptoms of COVID-19 (AOR = 2, CI: 1.3-3.2), and stress was associated with having symptoms of COVID-19 infection among family members (AOR = 1.9, CI: 1.3-3). Altered sleep was a potential risk factor for developing stress, anxiety, and depression symptoms. Manual thematic analysis of qualitative data generated four major themes, including the perception of fear of COVID-19, the perception of mental health impacts during COVID-19, the change in the medical curriculum along with the pandemic, and recommendations from the medical students to support the mental health concerns of medical students during public health crises like this pandemic. Qualitative findings showed that the participants experienced fear of their parents becoming infected by COVID-19, and this fear was more prominent in those who had their loved ones hospitalized. They were also stressed and anxious, with thoughts of death. Their fear also extended to their thoughts on academic progress and the effectiveness of online classes. Conclusion A substantial proportion of medical students experienced mental health difficulties in Bangladesh. Appropriate interventions should be designed, and adequate support should be provided to the medical students to protect their mental health and wellbeing, considering their potential impact on the future health system in a low-resource setting like Bangladesh.